Feasibility Study of the Development of a Drinking Water Supply System (SPAM) Investment of Cibulakan Springs Perumda Drinking Water Tirta Rahaja Bandung District – West Java - Sundana, Hari; Oetomo, Wateno; Marleno, Risma (LPPM of NAROTAMA UNIVERSITY, 2024)
Along with population growth and rapid development in Bandung Regency, demand for clean water is increasing. The development of a clean water supply system for Perumda Drinking water Tirta Raharja certainly requires a study of the feasibility of investing in the development of a drinking water supply system (SPAM) from the Cibulakan spring of Perumda Drinking Water Tirta Raharja, Bandung district so that it can be known to what extent the process is beneficial for the community and of course for the Government. The settlement method in this calculation for Feasibility Investment Analysis uses the Net Present Value (NPV) method and the Break Event Point (BEP) method. From the results of the investment feasibility analysis from the financial aspect with the Net Present Value (NVP) investment assessment, an NPV value of IDR 518,181,911,866 (NPV > 0) was obtained. So, the development of a Drinking Water Supply System (SPAM) from the Cibulakan springs of the Tirta Raharja Drinking Water Company, Bandung Regency is worth continuing. An NPV value that is positive or greater than (> 0) indicates that the income is greater than the value invested. The results of the Break Even Point (BEP) investment assessment showed that the return value occurred in the 14th year with the accumulation of negative profits being marked as positive after the 14th year. This explains that the investment in developing a Drinking Water Supply System (SPAM) from the Cibulakan springs of Perumda Drinking water Tirta Raharja in Bandung Regency is worth running, because there is a return on investment as proven by the BEP value for 7 years.